Pengelolaan Pemasaran Kelompok Bermain sebagai Upaya Menarik Minat Orang Tua Peserta Didik di KB-RA Baitul Muttaqien - Alfidea, Viona Sefi; Nugroho, Rivo (J+PLUS UNESA, 2024)
The purpose of this research is to describe marketing management and parents' interest in Baitul Muttaqien Playgroup. The research method used is descriptive qualitative with data collection techniques of interviews, participatory observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing. The result of this study is that reality marketing management has four components with a people component that refers to the human resources of the institution which is one of the two components of attracting parents of students. Programs are related to the products provided in the form of educational services as a component that attracts the interest of parents of students. The interest of parents of students is dominated by referential interest and preferential interest. Referential interest is shown through the tendency to refer Baitul Muttaqien Playgroup to people around. The preferential interest is the tendency of parents of learners in choosing an educational institution by referring to the criteria of each parent.